Training on Making Eid Greeting Cards in Fostering the Islamic Spirit of Students of Amin Sungai Besi Indah Guidance Studio, Selangor Malaysia - Lia Ariska Ritonga; Usmaidar Usmaidar; Novika Afridaini; Siti Nur Fadhilah (International Journal of Islamic Educational Research, 2025)
Amin Sungai Besi Indah Guidance Studio is a learning place for children of Indonesian workers (TKI) in Malaysia which aims to provide informal education, but limited resources and conventional learning methods are obstacles in efforts to improve the creative skills of children there. Therefore, innovation in creativity is needed that can attract children's interest and help them develop their creative abilities in a fun and meaningful way. Eid al-Fitr is a holiday for Muslims after fasting for 30 consecutive days. Where the moment of Eid al-Fitr is a very sacred moment for Muslims. In the celebration of the holiday, many families gather to forgive each other and also give greetings. Greeting cards are cards used to give greetings or words that are made in such a way to be creative using handicraft creations. In your speech, you can use cards that have been made, where there are handwritten words and decorated as attractively as possible. For buses we hand over cards to anyone we want to give them.